PREVALANCE AND CORELATES OF DEPRESSION AMONG CHRONIC KIDNEY DISEASE PATIENTS ON MAINTANCNE HEMODIALYSIS IN HYDERABAD AND ADJOINING AREA. (Pakistan Journal of Kidney Diseases, 2024)
BACKGROUNDDepression as the most prevalent and economically impactful chronic ailment Among HD patients, depression emerges as the foremost and gravest psychopathological consequence. It has extensive effect on quality of life, potentially resulting in severe consequences like discontinuation of HD treatment if not addressed.OBJECTIVE:To examine the risk factors and prevalence of depression in hemodialysis patients.METHODOLOGYA descriptive study was conducted at the Hemodialysis unit Department of Nephrology's Liaquat University Hospital  between April 15, 2021, and October 14, 2021, , involving 113 End-Stage Renal Disease (ESRD) patients on hemodialysis for over 3 months. Depression evaluation was performed through the Beck Depression Inventory (BDI-II) questionnaire.RESULTSOut of the 113 individuals involved, 54.9% were male while 45.1% were female, with a mean age of 41.99 ± 13.65 years and a mean hemodialysis duration of 15.44 ± 15.06 months. Among people with end-stage renal disease (ESRD), diabetes was the main cause in 43.4% of the patients. Regarding depression levels, 7 participants (6.2%) scored in ups and down, 22 (19.5%) experienced Mild Mood Disturbance, 23 (20.4%) were classified with Borderline Clinical Depression, 31 (27.4%) had Moderate Depression, and 30 (26.5%) were diagnosed with Severe Clinical Depression based on the Beck Depression Inventory (BDI-II) scoring system. CONCLUSIONIn conclusion, our study revealed that hemodialysis patients had a significant prevalence of depression. Notably, depression was linked to a higher risk of male gender, marital status, and current smoking.KEY WORDSEND STAGE RENAL DISEASE, CHRONIC KIDNEY DISEASE,DEPRESSION, HEMODIALYSIS.
Keywords: End stage renal disease; depression; hemodialysis; chronic kidney disease; Beck Dpression Inventory